Coupling of longitudinal optical phonon-plasmon in InGaN semiconductor layers - Phước, Dương Đình; Thảo, Đinh Như (Hue University Journal of Science: Natural Science, 2021)
The existence of longitudinal optical (LO) phonon-plasmon coupled modes in InGaN semiconductor layers is investigated by using the dielectric function theory. By using a p-polarized infrared wave irradiating obliquely on thin semiconductor layers, we observe the appearance of four distinct minima in the transmission spectrum of the material. The first two minima are given to the transverse optical phonon modes of the two InN and GaN component semiconductors, while the remaining two minima are attributed to the LO phonon-plasmon coupled modes. Besides, for the first time we have derived an equation for numerically calculating the frequencies of these coupled modes. Besides, the effect of electron density on LO phonon-plasmon coupled modes is also examined in detail.